Halal Logo And The Confidence Level Of Malaysian Customers On Indonesian Halal Certified Products - Jamal Abdul Nassir Shaari; Muhammad Khalique; Haslan Ottot (Allied Business Academics, 2024)
Indexed by SCOPUS/ERA